Enhancing Culinary Training with Spatial Augmented Reality: A User Study Comparing sAR Kitchen and Video Tutorials - Ghasemi, Yalda; Bayro, Allison; MacDonald, Justin; Jeong, Heejin; Reynolds, Joel; Nam, Chang S. (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
This paper presents sAR Kitchen, a cooking assistant that aims to enhance culinary training through the use of spatial augmented reality (sAR). We conducted a user study with twenty-two participants to investigate the effects of instructions given by our proposed sAR system and a monitor display with video tutorials in a playdough-making task representing the cooking task. Our study measured participants' perceived workload, usability, and performance regarding task completion time, product quality, and cooking station messiness. The results showed that sAR significantly decreased the perceived workload and increased the system's usability compared to traditional video-based tutorials. Additionally, our open-ended questions revealed that participants found the sAR instructions more engaging and interactive. Overall, this study demonstrates the potential of sAR to provide more user-friendly learning methods in culinary training.